Studi Tentang Analisis Pelayanan Perizinan dan Non Perizinan Berbasis Online Pada Masa Pandemi Covid-19 Di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Samarinda - Citrasari, Lianovi; Idris, Adam; Saleh, Muhammad Hairul (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
The research aims to describe and analyze online-based licensing and non-licensing services during the Covid-19 pandemic at the Investment and One-Stop Services Office of Samainda City. Data collection was carried out by means of library research and field research using observation, interviews and documents. The results of the study show that online-based licensing and non-licensing services during the Covid-19 pandemic in implementing electronic government did not fully apply the principles and benefits of e-government. The requirements can be accessed via the website, licensing application and whatsapp application. Regarding requirements, there is consistency in document equality. Furthermore, in online-based licensing and non-licensing service procedures, they still use conventional service operational standards. At the time of service, the issuance of online-based licensing and non-licensing does not affect service time. Furthermore, at the financing stage, the cost clarity criteria have been met. Service products during the Covid-19 pandemic had an impact on decreasing the number of licenses and non-licensing issued and had fulfilled the principle service criteria, namely service products, received correctly, correctly and legally and had legality or legal certainty. In the process of dealing with complaints, they become facilitators and mediators. Public opinion with online-based services felt convenience but also found several complaints in carrying out online-based services during the Covid-19 pandemic.